A biotin-avidin labeled enzyme immunoassay for the quantitation of serum TSH using protein-layered solid phase - Choi, MJ; Song, EY; Chung, TW (PHARMACEUTICAL SOCIETY KOREA, 1998)
A sensitive enzyme immunoassay for serum TSH has been developed utilizing the tight binding between biotin and avidin, and three layered protein polystyrene beads as solid phase. To increase binding capacity of TSH and sensitivity of the assay, the polystyrene beads were coated sequentially with mouse immunoglobulin as first layer, rabbit antimouse immunoglobulin as second layer and monoclonal anti-TSH as third layer. A serum sample was incubated simultaneously with a monoclonal anti-TSH immobilized polystyrene beads and a second monoclonal anti-TSH covalently attached to biotin. After washing, the antibody bound serum TSH-anti-TSH-biotin complex is reacted with horseradish peroxidase (HRP)-labeled avidin. Following a second wash, the bound HRP activity was measured colorimetrically. Reproducible results were obtained within 4 hours for serum TSH in the range between 0 mu lU/ml and 50 mu lU/ml with detection limit of 0.1 mu lU per test.